2014
DOI: 10.1002/oby.20841
|View full text |Cite
|
Sign up to set email alerts
|

Early weight loss while on lorcaserin, diet and exercise as a predictor of week 52 weight‐loss outcomes

Abstract: Objective: To identify an early treatment milestone that optimizes sensitivity and specificity for predicting 5% weight loss at Week (W) 52 in patients with and without type 2 diabetes on lorcaserin or placebo. Methods: Post hoc area under the curve for receiver operating characteristic analyses of data from three phase 3 trials comparing lifestyle modification1placebo with lifestyle modification1lorcaserin. A total of 6897 patients (18-65 years; BMI, 30-45 or 27-29.9 kg/m 2 with 1 comorbidity) were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…(profiles 2 and 3) compared profile 1. This observation is in agreement with numerous reports suggesting an association between greater initial weight loss and long-term success in response to both behavioral interventions alone (5, 9, 12, 14, 5964) or when behavioral interventions are combined with weight loss medications (65, 66). For example, results from the Look AHEAD trial indicated weight loss at 1-year was a strong determinant of 4-year weight loss (61).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…(profiles 2 and 3) compared profile 1. This observation is in agreement with numerous reports suggesting an association between greater initial weight loss and long-term success in response to both behavioral interventions alone (5, 9, 12, 14, 5964) or when behavioral interventions are combined with weight loss medications (65, 66). For example, results from the Look AHEAD trial indicated weight loss at 1-year was a strong determinant of 4-year weight loss (61).…”
Section: Discussionsupporting
confidence: 93%
“…In a primary care based translation of the DPP lifestyle intervention Yank et al (4) reported that only participants who lost ≥ 5% of baseline weight at 3 months were able to maintain this weight loss at 15 months. Smith et al (66) combined data from 3 separate phase 3 trials of lifestyle modification plus Locaserin (n= 6897) in adults. Results indicated that weight loss > 5% at week 12 was a strong predictor of weight loss at 1 year in adults with and without type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown that weight loss by week 12 with lorcaserin is a strong predictor of longer-term (52 weeks) success (47), which may indicate a good time at which to determine individual differences in response to lorcaserin. Overall, these results are strong and indicate clear changes in brain responses to food cues with lorcaserin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…10% weight loss of 85.5% and 49.8% (without T2D), and 70.5% and 35.9% (with T2D). 43 CM effects. A meta-analysis on secondary outcomes showed that compared with placebo, lorcaserin decreased mean waist circumference by 2.51 cm, systolic BP (SBP) by 0.61 mm Hg, diastolic BP (DBP) by 0.49 mm Hg, with no significant difference in heart rate (HR).…”
Section: Lorcaserinmentioning
confidence: 99%
“…However, increasingly in evaluating efficacy of drugs, responder populations can be defined early and may serve to limit exposure of nonresponsive patients to drug and selectively enhance outcomes. 43 Regulatory authorities increasingly require a weight loss threshold for continued medication as part of the product license.…”
Section: Attrition Rates In Trials and Clinical Practicementioning
confidence: 99%